Designing Mobile Electronic Books as a New Model of Providing Learning Contents for Medical Sciences - Majid Zare Bidaki; Ali Rajabpour Sanati; Amir Rahmanian Sharifabad (Kerman University of Medical Sciences, 2012)
Background & Objectives: Mobile technology has provided valuable opportunity for educational planners teachers and students to use it as a continuous process of teaching - learning Mobile books are sources of educational assistance that can be installed and viewed on mobile phones however there has been already no plan for production and use of them in the universities of Medical Sciences in Iran This study aimed to produce mobile books and assess students attitudes towards this model of learning Methods: First a Javabased electronic book maker software meeting the requirements and specifications of mobile phones was designed Then multimedia learning contents chosen from four medical and paramedical courses were converted and prepared as four mobile books In the next step the attitudes of 158 medical and paramedical students toward mobile learning were collected through a pretest Then the mobile books were installed on mobile cell phones of 106 students to be used by them during the semester At the end of the semester the views of all students toward mobile learning were asked again Data were analyzed using paired and independent ttest Results : According to the results use of mobile books significantly caused a positive attitude and enthusiasm towards elearning (p